Impact of Mother Tongue Pronunciation and Motivation on the Speaking Skills of EFL Learners: A Study at BS Level - Arooj, Sirat Ul; Zahid, Zohaib; Ramzan, Fozia (Pakistan Languages and Humanities Review, 2024)
The effect of motivation and native-language pronunciation on the oral communication abilities of undergraduate-level English as a foreign language (EFL) students is examined in this study. The purpose of this research is to better understand the challenges these students face while trying to speak English and how their native language influences their pronunciation. Also, the research is aiming to find out how much of an influence mother tongue and motivation to learn English have on EFL students’ speaking abilities. In order to accomplish these goals, the researcher meticulously crafted a 33-item questionnaire that focused on mother tongue, motivation, and speaking abilities. In the conclusion, this research gives useful advice for improving EFL students’ speaking abilities and shines light on the important topic of mother tongue interference and the influence of motivation on these skills. The results of this study potentially have far-reaching implications for EFL students